Multiagent induction chemotherapy followed by chemoradiation is associated with improved survival in locally advanced pancreatic cancer. Issue 19 (16th June 2017) - Torgeson, Anna; Lloyd, Shane; Boothe, Dustin; Tao, Randa; Whisenant, Jonathan; Garrido‐Laguna, Ignacio; Cannon, George M.
Abstract : BACKGROUND: The role of chemoradiotherapy (CRT) in locally advanced pancreatic cancer (LAPC) is uncertain after multiple randomized clinical trials have yielded mixed results. The authors used the National Cancer Data Base (NCDB) to determine whether CRT yields a survival benefit compared with chemotherapy alone (CT). METHODS: Patients with nonmetastatic LAPC diagnosed during 2004 through 2014 were identified in the NCDB. Patients who received CT were compared with those who received CRT using chi‐square analysis. Univariate and multivariate Cox regression analyses were used to compare demographic, clinical, and treatment characteristics that were predictive of survival. Propensity score matching and shared frailty analysis were done. Subgroup analyses were undertaken to examine patients who underwent pancreatectomy and cohorts of patients who received different CT or CRT regimens. RESULTS: In total, 8689 patients with LAPC were identified. CRT was associated with improved survival (median survival [MS], 13.5 months) compared with CT (MS, 10.6 months) on multivariate analysis (hazard ratio [HR], 0.80; P < .001). Induction chemotherapy before CRT (HR, 0.67; P < .001) and multiagent chemotherapy (HR, 0.72; P < .001) were also identified as independent predictors of survival compared with concurrent CRT and single‐agent CT, respectively. Patients in the CRT group who received multiagent induction chemotherapy had superior MS and pancreatectomy rates (MS, 17.5 months; HR, 0.70; P < .001; pancreatectomy rate, 10%) compared with those who received multiagent CT alone (MS, 12.4 months; pancreatectomy rate, 3.3%). Patients who underwent pancreatectomy experienced improved survival (MS, 22 vs 10.6 months; HR, 0.39; P < .001). CONCLUSIONS: In this NCDB analysis, maximizing systemic chemotherapy before CRT improved survival compared with CT alone in patients with LAPC. Continued analysis of CRT in properly selected patients after maximized systemic therapy is needed. Cancer 2017;123:3816‐24 . © 2017 American Cancer Society . Abstract : Patients with locally advanced, unresectable pancreatic cancer who undergo either chemoradiation or chemotherapy only are compared in the National Cancer Data Base. Multiagent chemotherapy followed by chemoradiation is associated with improved survival and pancreatectomy rates compared with chemotherapy alone and radiotherapy with concurrent chemotherapy.